Protection of Copyright and Accessing Education Materials at Low Prices: Finding a Sustainable Solution for Bangladesh - Islam, Mohammad Towhidul; Zaman, Moniruz (Dhaka University Law Journal, 2022)
Abstract not available Dhaka University Law Journal, Vol. 32(2), 2021 P.49-68